Human Rights in the Oil and Gas Industry: When Are Policies and Practices Enough to Prevent Abuse?. Issue 6 (July 2022) - Olsen, Tricia; Rehbein, Kathleen; Snelson-Powell, Annie; Westermann-Behaylo, Michelle
Multinational enterprises are aware of their responsibility to protect human rights now more than ever, but severe human rights violations, including physical integrity abuses (e.g., death, torture, disappearances), continue unabated. To explore this puzzle, we engage theoretically with the means-ends decoupling literature to examine if and when oil and gas firms' policies and practices prevent severe human rights abuse. Using an original dataset, we identify two pathways to mitigate means-ends decoupling: (a) while human rights policies alone do not reduce human rights abuses, firms with a high-quality human rights policy over the long-term reduce severe human rights abuses; (b) firms that combine preparedness—which we define as a firm's capabilities, practices, and engagement—with a long-term human rights policy also reduce the likelihood of human rights abuses. Preparedness, we argue, can lead to reinforcement dynamics between long-term policy efforts and additional capabilities that provide a more holistic understanding of firm behavior.